Kerajaan Huristak Tahun 1884-1966 - Heni Kiki Daulay; Laila Rohani; Nabila Yasmin (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
This research was conducted because there are several problems, namely regarding the lack of knowledge of the public and the general public about the Huristak Kingdom especially regarding the historical events that occurred in 1884-1966, the royal heritage at that time and regarding the great contribution of the Huristak Kingdom in terms of fighting for the independence of the Unitary Republic of Indonesia. Indonesia (NKRI) using historical research methods as well as philological and archaeological theories by observing the remains of the Huristak Kingdom such as manuscripts, hairy spears, dragon swords, dragon daggers, cannons, snake bracelets, Bagas Godang, Sopo Godang, King Huristak's funeral and family Kingdom of Huristak, photos of Patuan Barumun, and photos of ships on the Barumun River. The Huristak kingdom was descended directly from Sultan Iskandar Zulkarnain in the Land of Rum who was descended directly from the Kushan Empire in North India. The Kings of the Huristak Kingdom to date are Ompu Suhataon, Sutan Gadoe Mulia, Dja Mangalengkung Dja Lela I, Dja Lela II, Kali Omar, Sultan Nalobi, Sutan Palaon, Patuan Barumun, Sutan Managor, Patuan Nagalan, Patuan Tondi Hasibuan. The Patuan Barumun Raja IX Huristak went through 4 important periods, namely the Dutch East Indies period, the Japanese Period, the Independence Period and the Dutch Military Aggression II period. During the Second Dutch Military Aggression, Patuan Barumun, who was an advisor to the corps with combat headquarters in Gunung Tua, handed over the red and white saka before the start of the war. Donating rice during the war.